Digital Native(ness), Mobile Technologies and Language Proficiency in Underdeveloped Countries - Valentin Uwizeyimana (Register Journal, 2018)
Various studies have elaborated on the concept of ‘digital native(ness)’, i.e. (an identity of) the generation of students who were born during the digital technology era, i.e. from the 1980s onwards (Prensky 2001). Those studies claim that digital natives have been exposed to modern technologies, and thus are familiar with using them in their everyday activities (Dang 2013; Jacobson Turner 2010). Those studies do not go beyond the access to and the general use of technologies. They ignore the fact that the ability to use technologies for personal purposes does not represent the ability to use them for educational and other specialized purposes (Stockwell Hubbard 2013:4). Furthermore, there is a gap in terms of technological devices and geographical locations which were considered by those studies (Burston 2014; Thinyane 2010; Brown Czerniewicz 2010). In these regards, by using a proficiency test and a survey with 60 digital natives from an underdeveloped country, this study investigated the effect of mobile technologies in language learning (MTLL) on English proficiency. In terms of English proficiency, this study found no significant difference among the participants, although some of them were making use of MTLL whereas others were not. With the fact that MTLL have the potential to improve the language proficiency (Park Slater 2014; Alotaibi, Alamer Al-Khalifa 2015; Stockwell Liu 2015), this article recommends how teachers should provide guidance and assistance to the learners in order to benefit from modern technologies.Keywords: Digital native(ness); Mobile technologies in language learning (MTLL); English proficiency test (EPT)